Environmental factors influencing tick densities over seven years in a French suburban forest. Issue 1 (December 2016) - Paul, Richard; Cote, Martine; Le Naour, Evelyne; Bonnet, Sarah
Abstract Background Worldwide changes in socio-economic and environmental factors and the global climate are recognised causes of variation in tick distribution and density. Thus it is of great importance that new studies address the changing risk of infection for exposed populations. In Europe, Ixodes ricinus ticks are the most common vectors of several pathogens impacting veterinary and public health that have colonised suburban habitats. Methods This study aimed to evaluate longitudinalI. ricinus questing densities and infection rates over 7 years in a French suburban forested area with high human population density. Ticks were collected in spring yearly between 2008 and 2014 and, out of a total of 8594 collectedI. ricinus, a representative subset of adult females (n = 259) were individually examined for the presence of several pathogens via PCR. Results Nymph densities peaked in 2009–2011, and then declined in 2012–2014. Changes in monthly temperature only had a modest impact on this variation. In contrast, analysis revealed a complex intra-annual relationship between mean nymph density and both concurrent and lagged mean monthly temperatures. The following pathogens were detected in the studied area:Anaplasma phagocytophilum, Rickettsia helvetica, Babesia venatorum andB. divergens, Francisella tularensis, Borrelia miyamotoi, B. afzelii/valaisiana, B. garinii/lusitaniae andBartonella spp. Conclusion Our findings reinforce the conclusion that ticks are important vectors of pathogenic microorganisms in suburban forests and suggest that despite complex intra-annual relationships between tick densities and temperature, there is no evidence for a climate-associated increase in infection risk over the 7-year period. Rather, tick densities are likely to be strongly influenced by population density fluctuations in vertebrate host species and wildlife management. Further detailed studies on the impact of climate change on tick population densities are required.